2015
DOI: 10.1007/s10068-015-0132-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low frequency (20–35 kHz) airborne ultrasonication on microbiological and physicochemical properties of soybean Koji

Abstract: The effect of low frequency airborne ultrasound energy on microbiological and physicochemical properties of soybean koji during preparation was investigated. Following inoculation of steam-heated soybeans with spores of Aspergillus oryzae, koji samples were treated with airborne sonication at increasing frequencies of 20, 25, 30, and 35 kHz and incubated at 30 o C for 5 days. Amylase and protease activities, the number of fungal spores, bacterial growth, the moisture content, pH, and the titratable acidity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…When the sonication frequency was close to the resonant frequency of rapeseed protein solution, the cavitation effect was stronger on the sample. 26 By increasing sonication time from 10 to 30 min, the content of LAL in rapeseed protein treated with different pH values decreased. When the sonication time continued to increase, the content of LAL increased again, as shown in Figure 1C.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…When the sonication frequency was close to the resonant frequency of rapeseed protein solution, the cavitation effect was stronger on the sample. 26 By increasing sonication time from 10 to 30 min, the content of LAL in rapeseed protein treated with different pH values decreased. When the sonication time continued to increase, the content of LAL increased again, as shown in Figure 1C.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Following ultrasound frequencies treatment, results (Figure A, B) indicated that the inhibition effect of fixed frequency 28 kHz was better than that of other frequencies because the LAL content was the lowest. When the sonication frequency was close to the resonant frequency of rapeseed protein solution, the cavitation effect was stronger on the sample …”
Section: Resultsmentioning
confidence: 99%
“…We assumed that the decrease of the moisture content in koji was probably due to consumption of water by Aspergillus growth as well as through evaporation. 18 The multivariate analysis for various rice koji extracts based on GC−TOF−MS data sets indicated a fermentation timecorrelated metabolic profile for primary metabolites, regardless of the DOM (Figure 1A). On the other hand, the multivariate analysis based on UHPLC−LTQ−IT−MS/MS data sets showed a secondary metabolite profile depending upon various DOMs of rice substrates (Figure 1B).…”
Section: Discussionmentioning
confidence: 98%
“…There were no significant differences observed for mold growth and sporulation among the koji samples with five different DOMs. We assumed that the decrease of the moisture content in koji was probably due to consumption of water by Aspergillus growth as well as through evaporation …”
Section: Discussionmentioning
confidence: 99%
“…Although, it's not clear mechanism how affect enzyme hydrolysis, similar phenomenon had been found in electromagnetic wave. Byeon et al (29) reported that stimulation by ultrasonication at 20-35 kHz during fermentation of soybean koji greatly increased the amylase activity. Irradiation of the seed embryos of Isatis indigotica Fort with He-Ne laser (5.23 mW/mm 2 , 5 min) and microwave (1.26 mW/mm 2 , 8 s) significantly increased the activities of α-amylase and the total amylase content in the seed embryos relative to that in un-irradiated controls (30).…”
Section: Resultsmentioning
confidence: 99%